2015
DOI: 10.1049/iet-nbt.2015.0008
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin‐silver nanoparticle formulations enhance the cellular uptake of plumbagin and its antiproliferative activities

Abstract: Colloidal silver nanoparticles (AgNPs) have attracted much attention in recent years as diagnostics and new drug delivery system in cancer medicine. To study the effects of plumbagin (PLB), a relatively non-toxic napthaquinone isolated from the roots of Plumbago indica in human cervical cancer cell line and developed a formulation to enhance its cytotoxic activities. Silver nanoparticles were synthesised by chemical reduction method and complexed with PLB. Both the AgNPs and the complex PLB-AgNPs were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…This result correlated well with those obtained from the antiproliferative assay, showing that Tf‐bearing liposomes exhibited the highest antiproliferative effect on B16‐F10 cells followed by A431 and T98G cells. Our results were in agreement with previous reports which demonstrated that the treatment with plumbagin entrapped in silver nanocages led to the apoptosis of A431 cells (Duraipandy et al, ) and HeLa cells (Appadurai & Rathinasamy, ), unlike free plumbagin.…”
Section: Discussionsupporting
confidence: 94%
“…This result correlated well with those obtained from the antiproliferative assay, showing that Tf‐bearing liposomes exhibited the highest antiproliferative effect on B16‐F10 cells followed by A431 and T98G cells. Our results were in agreement with previous reports which demonstrated that the treatment with plumbagin entrapped in silver nanocages led to the apoptosis of A431 cells (Duraipandy et al, ) and HeLa cells (Appadurai & Rathinasamy, ), unlike free plumbagin.…”
Section: Discussionsupporting
confidence: 94%
“…The application of plumbagin in cancer therapy has been limited due to its low aqueous solubility and the side‐effects. Nano‐drug delivery systems and other pharmaceutic strategies may encapsulate plumbagin effectively to overcome poor water solubility, prolong circulation half‐life time, reduce the side‐effects, and ameliorate the anticancer efficacy . Also, a great amount of efforts have been dedicated to the development of plumbagin derivatives for the purpose of improving molecular properties and pharmacological profile .…”
Section: Miscellaneousmentioning
confidence: 99%
“…systems and other pharmaceutic strategies may encapsulate plumbagin effectively to overcome poor water solubility, prolong circulation half-life time, reduce the side-effects, and ameliorate the anticancer efficacy. [68][69][70] Also, a great amount of efforts have been dedicated to the development of plumbagin derivatives for the purpose of improving molecular properties and pharmacological profile. [71] Shikonin is another plant-based secondary metabolite belonging to 1,4-naphthoquinone and is extracted from the root of Lithospermum erythrorhizon.…”
Section: Miscellaneousmentioning
confidence: 99%
“…For the phytochemical plumbagin, silver nanoparticles were synthesized to overcome the lack of sensitivity and selectivity towards cancer cells, and such formulation reduced the effective concentration required to induce apoptosis to half of the free compound [ 204 ] in addition to enhancing the cellular uptake [ 205 ]. The reduced toxicity in normal cells, and better bioavailability of nanoformulated plumbagin has been reported by another independent group as well [ 206 ].…”
Section: Challenges For Phytochemicals In Cancer Therapy and Emergmentioning
confidence: 99%